Computational Evidence for the Reactivation Process of Human Acetylcholinesterase Inhibited by Carbamates - Silvia Matos, Karina; F. F. da Cunha, Elaine; Abagyan, Ruben; C. Ramalho, Teodorico (Combinatorial Chemistry & High Throughput Screening, 2014)
Acetylcholinesterase (AChE) is responsible for hydrolysis of acetylcholine (ACh), a function, which if disrupted, leads to cholinergic syndrome. Carbamates (CB) and organophosphorus compounds (OP) are AChE inhibitors, toxic and capable of causing severe poisoning or death to exposed individuals. The AChE reactivation is considered the main function of the oximes. In case of poisoning by CB, there is no consistent data in the literature for an oxime reactivation mechanism. In this work, we evaluated the affinity and reactivity of oximes with activity already reported against AChE inhibited by the OP chemical warfare agent ciclosarin, with MmAChE and HsAChE active sites inhibited by the CB pesticide carbofuran. Thus, our theoretical data indicate that HLO-7, BI-6 and K005 compounds may be promising reactivators of AChE inhibited by carbofuran.
Keywords: Docking studies